Denture Base Materials Wettability With Natural And Artificial Saliva - Alexandru Titus Farcasiu; Mihaela Pauna (Romanian Society of Oral Rehabilitation, 2011)
The system composed by mucosa, saliva and denture is complex and dependent of many variables. The decreased or absent flow of saliva induces a high disconfort which has to be reduced by all means, this meaning use of artificial saliva and improvement of surface characteristics of the denture base material. We investigated five materials produced by classic tehnology (press-pack moulding + different heat polymerization cycles) and two injection-type materials. The wettability was appreciated by contact angle measurements using a computer-controlled system (CAM 101, KSV Instruments). The natural saliva presented a contact angle between 70-81° while artificial saliva has better angles (41-51°). Statistic analysis performed by SPSS 10 for Windows shows significant differences between materials regarding both salivas involved. The confidence intervals are large for most of the measurements which could be explained by the inhomogenous structures of materials. Biodentaplast has very good wettability with artificial saliva, followed by BMS 014 and Superacryl. Eco Cryl Hot wets best with natural saliva, followed by Acry Pol Plus and Biodentaplast.